The prevalence of developmental dyscalculia in Brazilian public school system - Bastos, José Alexandre; Cecato, Angela Maria Traldi; Martins, Marielza Regina Ismael; Grecca, Kelly Regina Risso; Pierini, Rafael (Arquivos de Neuro-Psiquiatria, 2016)
The goal of the study was to assess public school children at the end of the first stage of elementary school. We used a protocol applied concurrently with a writing test in the form of an unexpected activity in 28 public schools; 2,893 children assessed, 687 exhibited performance below 58 points, 184 were excluded due to change of address or lack of consent; 503 children subjected to a test of intellectual capacity and reading assessment and 71 considered intellectually disabled were excluded. 226 (7.8%) children, who could read, write, and had normal intellectual level, met the criteria of developmental dyscalculia (DD), 98 female and 128 male. The most influential factors in the prevalence were socioeconomic levels of the schools neighborhood, education level of parents, and being male, as demonstrated by the odds ratio and multiple logistic regression analysis. Further studies should be done so that educational policies are taken.
Keywords: dyscalculia; epidemiology; prevalence; children; socioeconomic status; multivariate analysis